A Fast and Reliable Balanced Approach for Detecting and Tracking Road Vehicles - Farag, Wael (Recent Advances in Computer Science and Communications, 2022)
Introduction: An advanced, reliable and fast vehicle detection-and-tracking technique is proposed, implemented and tested. In this paper, an advanced-and-reliable vehicle detectionand- tracking technique is proposed and implemented. The Real-Time Vehicle Detection-and- Tracking (RT_VDT) technique is well suited for Advanced Driving Assistance Systems (ADAS) applications or Self-Driving Cars (SDC). Methods: The Real-Time Vehicle Detection-and-Tracking (RT_VDT) is proposed, and it is mainly a pipeline of reliable computer-vision and machine-learning algorithms that augment each other and take in raw RGB images to produce the required boundary boxes of the vehicles that appear in the front driving space of the car. The main emphasis is the careful fusion of the employed algorithms, where some of them work in parallel to strengthen each other in order to produce a precise and sophisticated real-time output. Results: The RT_VDT is tested and its performance is evaluated using actual road images and videos captured by the front-mounted camera of the car as well as on the KITTI benchmark. The evaluation of the RT_VDT shows that it reliably detects and tracks vehicle boundaries under various conditions. Discussion: Robust real-time vehicle detection and tracking is required for Advanced Driving Assistance Systems (ADAS) applications or Self-Driving Cars (SDC).
Keywords: vehicle detection